ANALISIS TINGKAT KELAYAKAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN KERJA BENGKEL DAN GAMBAR TEKNIK KELAS X TEKNIK AUDIO VIDEO DI SMK NEGERI 1 SUMATERA BARAT - Hidayati Armi; Ika Parma Dewi (Universitas Negeri Padang, 2020)
This study aims to determine the analysis of the feasibility level of interactive learning media in Workshop Work and Engineering Drawing Subjects for Class X Audio Video Engineering at SMK Negeri 1 West Sumatra. The method used in this research is the descriptive method using quantitative and qualitative approaches. The types of data used in research are quantitative data and qualitative data. The research instrument in the form of a questionnaire was used to obtain data about the level of validity of learning media. This questionnaire was filled in by two material experts and two media experts. The aspects that are validated in this study are the aspects of content (material) and aspects of display (media). The data analysis technique used is quantitative descriptive analysis and qualitative descriptive analysis. The results showed that interactive learning media obtained an average score of 87% from both material experts and 84% from both media experts. Based on the results of these studies interactive learning media in Workshop Work and Technical Drawing Subjects are in the